Comparing and Contrasting National REDD+ Strategies in the Hindukush Himalayan Region: Implications for REDD+ Implementation (Journal of Forest and Livelihood, 2018)
The paper compares and contrasts the national REDD+ (reducing emissions from deforestation and forest degradation and the role of conservation, sustainable management of forests and enhancement of forest carbon stocks in developing countries) strategies of the three Hindukush Himalayan countries (HKH), namely Nepal, India, and Myanmar. Through review of relevant literature and content analysis of the National REDD+ Strategy, this paper analyses the processes and contents of the strategies with key selected parameters. The review found that the countries have followed a similar pattern of consultative process in the development of REDD+ strategy. However, the strategies have largely focused on the direct drivers of deforestation and forest degradation (D&D), often with limited attention to the underlying causes. Likewise, the institutional arrangement for REDD+ implementation often lacks clarity at the local/community level. Notwithstanding to these shortcomings, the strategy of these countries have prioritised expansion of community-based forest management in order to meet the intended targets of carbon enhancement. We observed that both the process and contents of the Strategies reflects the institutional culture of the forest sector, major drivers of D&D and the status of forestry in relation to the country’s economy. The paper concludes that the policies and measures aimed at addressing the drivers of D&D should consider both direct and underlying causes. Moreover, expansion of community-based forest management should be considered whilst ensuring traditional/customary rights of the forest users.